The Lived Realities of Health Financing: A Qualitative Exploration of Catastrophic Health Expenditure in the Philippines - Lasco, Gideon (Archīum Ateneo, 2022)
Objectives: Within the last two decades, studies worldwide have documented catastrophic health spending and out-of-pocket expenditure in low- and middle-income countries like the Philippines. This study sought to unpack patients and their families' lived experiences in dealing with such financial challenges. Methods: This paper stems from a multi-sited qualitative project in the Philippines involving FGDs that sought to elicit people’s long-term health goals and the barriers they encounter in attaining good health. Focusing on the domain of health financing, we used principles of grounded theory to analyze how low and middle-income Filipinos pay for their health needs. Results: For many Filipinos, health financing often necessitates various actors' participation and entails predictable and unforeseen complications throughout the illness trajectory. We describe the lived realities of health financing through four domains: ‘pagtitiis’ (enduring the illness), ‘pangungutang’ (borrowing the money), ‘pagmamakaawa’ (soliciting help from the government and non-government channels), and PhilHealth—the State-owned national insurance agency—whose (non-)role figures prominently in catastrophic expenditure. Conclusion: Our paper illustrates how illness not only leads to catastrophic expenditure; expenditure-related challenges conversely account for poorer health outcomes. By exploring the health system through qualitative means, we identify specific points of intervention that resonate across LMICs (low and middle-income countries) worldwide, such as addressing predatory loan practices and ‘hidden’ costs; improving public health communications; expanding government insurance benefits; and bolstering health literacy to include health financial literacy in the school and community settings.